DEVELOPMENT OF FAIR TRADE IDEAS - Czarnecka, Adrianna (Torun International Studies, 2017)
The topic of the work below is the development of fair trade ideas over the years. By analyzing reports, websites, and newspaper reports, I have been able to compare the work of fair trade organizations. The social movement has transformed the activity into fully professional non-governmental organizations. However, the international and international institutions have become increasingly popular. The development of the concept has a significant impact on the quality of life of people in developing countries. Through the promotion of promotional and educational campaigns, the awareness of both consumers and small producers who are able to create their own networks increases. Idea Fair Trade turned out to be hope for the fight against poverty, disproportions in the world. Through trade we are able to support developing countries. The emergence of international organizations allows for the control of these processes, as well as the development of concept and control of activities. The aim of the article is to show the proces of developing and giving the idea of fair trade.